Fern-Allies and Ferns of Kameng District, Arunachal Pradesh - Rao, A. S.; Hajra, P. K. (Indian Forester, 1980)
The richness of the Pteridophytic flora of Kameng District, Arunachal Pradesh is emphasised, with an enumeration of 22 species of Fern-allies in 3 genera and 3 families; 214 species of Ferns in 71 genera, and 21 families.